Short-term Menhaden Oil Rich Diet Changes Renal Lipid Profile in Acute Kidney Injury - Ossani, Georgina Paula (2015)
Weanling male Wistar rats fed a choline-deficient diet develop acute kidney injury. Menhaden oil, which is a very important source of omega-3 fatty acids, has a notorious protective effect. The mechanism of this protection is unknown; one possibility could be that menhaden oil changes renal lipid profile, with an impact on the functions of biological membranes. The aim of this work was to study the renal lipid profile in rats fed a choline-deficient diet with menhaden oil or vegetable oil as lipids. Rats were divided into 4 groups and fed four different diets for 7 days: choline-deficient or choline-supplemented diets with corn and hydrogenated oils or menhaden oil. Serum homocysteine, vitamin B12, and folic acid were analyzed. Renal lipid profile, as well as the fatty acid composition of the three oils, was measured. Choline-deficient rats fed vegetable oils showed renal cortical necrosis. Renal omega-6 fatty acids were higher in rats fed a choline-deficient diet and a choline-supplemented diet with vegetable oils, while renal omega-3 fatty acids were higher in rats fed a choline-deficient diet and a choline-supplemented diet with menhaden oil. Rats fed menhaden oil diets had higher levels of renal eicosapentaenoic and docosahexaenoic acids. Renal myristic acid was increased in rats fed menhaden oil. The lipid renal profile varied quickly according to the type of oil contented in the diet.